Study on the drunkenness of Chinese Baijiu with representative flavor based on behavioral characteristics - Guo, Xuefeng; Cheng, Yuxin; Huang, Yongguang (Frontiers in Nutrition, 2022)
The essential role of the drunkenness on the healthy development of Chinese baijiu was studied in this research. This study revealed the effects of Baijiu on the behaviors of mice and to evaluate the degree of drunkenness of soy sauce-, strong-, light- and light and soy sauce-flavored Baijiu. The parameters obtained from the open field test were transformed into the behavioral drunkenness index by mathematical statistical analysis and the drunkenness-associated key compounds of Baijiu were analyzed. The results showed that strong- and light-flavored Baijiu presented higher levels of drunkenness and sobriety than soy sauce-flavored Baijiu. Interestingly, light and soy sauce-flavored Baijiu showed low drunkenness but a high sobriety degree. Specifically, the degree of drunkenness was positively correlated with fusel alcohol and aldehydes but negatively correlated with esters and acids. This study will enrich references for Baijiu behavior studies and lay a foundation for the research and development of healthy Baijiu.